The Emergence and Evolutionary Fate of DIversity Under Soft and Hard Selection - Chen, Patrick (Université d'Ottawa / University of Ottawa, 2018)
It has long been appreciated that genetic diversity can be stably maintained in spatially structured environments depending on the method by which subdivided populations are regulated. Theory suggests diversity in spatially heterogeneous environments can be stably maintained when populations are regulated at the level of each individual subpopulation (soft selection) rather than at the level of the total mixed population (hard selection). Although mathematically established decades ago, direct empirical tests of these predictions remain scarce, and its robustness to prolonged selection on evolutionary timescales remain unclear. Here, we track the emergence and fate of diversity in replicate laboratory populations of the opportunistic human pathogen, Pseudomonas aeruginosa, evolving in spatially structured environments composed of patches with or without antibiotic selection. We manipulate the scale of population regulation by transferring either a fixed number (soft selection) or volume (hard selection) of cells. We find that, while both forms of population regulation can lead to prolonged coexistence between resistant and sensitive strains, diversity is eventually lost by the evolution of broadly adapted resistant strains that pay lower costs of resistance. Notably, coexistence on average persists longer under soft selection than hard selection, consistent with the idea that soft selection is more effective at maintaining diversity than hard selection. Our results suggest that, in line with theory, the manner of population regulation can impact the maintenance of diversity and that the ecological conditions supporting diversity in the short term can be readily undermined by evolutionary processes in the long term.
Keywords: evolution; experimental; soft; hard; selection; pseudomonas; antibiotic; microbial